2016
DOI: 10.1097/hjh.0000000000000820
|View full text |Cite
|
Sign up to set email alerts
|

Hypertension awareness, treatment, and control among diabetic and nondiabetic individuals in a multiethnic population in the Netherlands

Abstract: Hypertension awareness and treatment rates are similar among ethnic groups in both diabetics and nondiabetics. Adequate BP control remains low among ethnic minorities, particularly among diabetic African origin people. Major effort is needed to improve BP control among diabetic people given the cardiovascular complications associated with uncontrolled BP in this group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…Around 40% of the population of Suriname lives in the Netherlands, where they face major inequities in health compared to white Dutch (Fernald et al, 2016;Snijder et al, 2017;Brewster, 2019;Diemer et al, 2020;Brewster, 2020;Kallianidis et al, 2022). Centuries of enslavement of African ancestry persons, as well as decades of indentured labour of Asian ancestry persons, still seem to resonate in the health of these population groups today (Stedman, 1796;Teenstra, 1842;de Kom, 1934;Davis, 2011;Oehlers et al, 2016;Schokkenbroek and van den Broeke, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Around 40% of the population of Suriname lives in the Netherlands, where they face major inequities in health compared to white Dutch (Fernald et al, 2016;Snijder et al, 2017;Brewster, 2019;Diemer et al, 2020;Brewster, 2020;Kallianidis et al, 2022). Centuries of enslavement of African ancestry persons, as well as decades of indentured labour of Asian ancestry persons, still seem to resonate in the health of these population groups today (Stedman, 1796;Teenstra, 1842;de Kom, 1934;Davis, 2011;Oehlers et al, 2016;Schokkenbroek and van den Broeke, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Surinamese persons have a lower life expectancy than European Dutch whether living in Suriname or in the Netherlands (Central Bureau of Statistics, www.cbs.nl; The World Bank, n.d.; Brewster, 2020). The lifespan of Surinamese-Dutch is up to 3 to 5 years shorter than European-Dutch, with higher child and maternal mortality (Central Bureau of Statistics, www.cbs.nl;Fernald et al, 2016;Snijder et al, 2017;Brewster, 2019;Diemer et al, 2020;Brewster et al, 2020;Brewster, 2020;Kallianidis et al, 2022). However, national public health research on inequities among Surinamese-Dutch is hampered by the lack of data segregated by ancestry (Brewster, 2019;2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Superdiversity underlines population complexity and fluidity, often utilising a geographical rather than ethno-national focus, avoiding the categorisation of populations by ethnic or country of origin (Cuthill 2017) and highlighting the multi-layered nature of populations in neighbourhoods where old and new migrants and minorities live with ethnic-majority native residents and where demographic changes have become the norm (Pemberton and Phillimore 2018). These complex and evolving populations offer a range of challenges for healthcare provision and health promotion, particularly given evidence of continuing disparities in health outcomes, even before the emergence of superdiversity (Hernandez-Plaza et al 2014;Bhopal et al 2014;Fernald et al 2016;Mladovsky 2009).…”
Section: The Emergence Of Superdiversitymentioning
confidence: 99%
“…Limited evidence is available about the association of SES with awareness, treatment and control of hypertension especially for migrant groups [3]. It has been shown that prevalence of hypertension is higher in ethnic minority groups in Europe [5][6][7][8], and that hypertension is more frequently uncontrolled compared with the host European populations [5,9,10]. This implies that ethnicity is an important factor to consider in hypertension management.…”
Section: Introductionmentioning
confidence: 99%